PSIX-34 Acclimating feedlot cattle: Effects on home pen behavior. (7th December 2018) - Parsons, R; Dewell, G; Dewell, R; Coetzee, J; Noffsinger, T; Johnson, A; Millman, S
Abstract: Cattle acclimation involves low stress handling to encourage cohesive herd formation within the home pen, moving the herd around the pen, followed by moving cattle through the processing facility. The aim is to familiarize cattle with experiences during husbandry and veterinary interventions. Our goal was to determine the effects of acclimation on cattle home pen behavior, with the hypothesis that acclimated calves display more feeding and resting. Upon arrival at the feedlot, calves were systematically assigned to control (C) or acclimated (A) treatments by pen (C=296 calves, 7 pens; A=352 calves, 7 pens total). Accelerometers were placed on three sentinel calves/pen. For A calves, acclimation was performed once daily on 3 days over a 10-day period, twice prior to and once following initial processing; C calves received no acclimation. Cameras mounted above each pen collected images at 5 time points daily (0600, 0800, 1200, 1600 and 1900) from D+1 through D+10 relative to calf arrival. Technicians blinded to treatment and day observed all calves in all images using the following ethogram: standing, feeding, lying and missing (obscured from view). A mixed model statistical analysis was used to assess behavioral differences, which included interaction of day and treatment, fixed effects of precipitation and covariate of temperature; P≤0.05 considered significant. Accelerometer data revealed no treatment differences for behavior (P>0.05), but C calf activity was higher on D+1 than A calves and decreased over time for C calves. Acclimation did not affect lying, standing or feeding behaviors (P>0.05). Missing calves were higher on days 1, 3, 5 and 10 in acclimated pens (P≤0.05). Cohesive groups formed by acclimated calves could explain this result, since identifying individual calves in acclimated pens was more challenging. In conclusion, we found some evidence to support acclimation but there was no increase in time spent feeding.